2021
DOI: 10.4018/joeuc.20210701.oa8
|View full text |Cite
|
Sign up to set email alerts
|

Review of Consumer-to-Consumer E-Commerce Research Collaboration

Abstract: This study uses a content analysis method to systematically review 83 research papers from 2002-2018 to explore consumer-to-consumer (C2C) e-commerce research trends. The findings of this study indicate that (1) C2C e-commerce is discussed and investigated in many disciplines, but mainly published in e-commerce journals; (2) studies on C2C e-commerce increasingly focus on diverse topics, but concentrate on regions such as China and the United States; (3) the focus of academic collaboration has shifted from dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
0
20
0
2
Order By: Relevance
“…Entrepreneurial education enables students that how to identify and exploit entrepreneurial opportunities in the market. It stimulates students to have greater information, knowledge, skills, and encouragement in supporting their entrepreneurial mindset to become entrepreneurs (Yuan et al, 2021). Entrepreneurial education enables the entrepreneurial mindset of the student to have a better perception of numerous results that are crucial for entrepreneurial startups.…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurial education enables students that how to identify and exploit entrepreneurial opportunities in the market. It stimulates students to have greater information, knowledge, skills, and encouragement in supporting their entrepreneurial mindset to become entrepreneurs (Yuan et al, 2021). Entrepreneurial education enables the entrepreneurial mindset of the student to have a better perception of numerous results that are crucial for entrepreneurial startups.…”
Section: Discussionmentioning
confidence: 99%
“…During COVID‐19, according to the International Labor Organization (2020), to ensure employee health and safety in the workplace, every organization should focus on four WSP components: the management's commitment to safety, safety training, safety regulations and procedures, and employee involvement. Previous studies have demonstrated that these practices have an impact on employee psychology, attitude, and behavior during COVID‐19 (Chi et al, 2020; Lee, 2021; Vu et al, 2022; Yuan et al, 2021). As a result, we used these four aspects to assess PWSPs during COVID‐19 for this research.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Moreover, as explained by the JD–R model, PWSPs regarded as job resources can buffer the impact of job demand (e.g., CV19PHR) on employees' burnout during the crisis. Yuan et al (2021) claimed that WSPs could assist workers in mobilizing their resources toward executing their job duties by mitigating the health and safety concerns posed by COVID‐19 and creating perceptions of a healthy and safe work environment. According to Yin and Ni (2021), supervisory safety support might reduce employee stress by lowering the perceived dread of external danger and boosting felt psychological safety, resulting in reduced avoidance coping behavior.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was another viewpoint: Although entrepreneurs' characteristics are personal, they can be cultivated by unconventional teaching methods (Kirby, 2004). Some scholars indicated that "In modern society, the role of education in cultivating entrepreneurs is underestimated, " because more than 90% of the successful founders of high-tech companies are college graduates, and more than half of them have graduate degrees (Marvel, 2013;Yuan et al, 2021). Wilson et al (2007) thought that entrepreneurship education can promote the generation of entrepreneurial intention (Zhang et al, 2014;Lv et al, 2021).…”
Section: Literature Review and Hypotheses Entrepreneurship Education And Entrepreneurial Intentionmentioning
confidence: 99%